(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article presents the results of a study of expert assessment of the choice of vital drugs and the adequacy of their daily dose, taking into account the indicators of therapeutic and pharmacoeconomic effectiveness of the course of various types of treatment for chronic liver diseases widely used in clinical practice by doctors.